Giving it all artistically: Observations on the 48th Maribor Theatre Festival: The move towards the grotesque as a sentiment of crisis. Issue 161 (1st March 2014) - Irmer, Thomas
This review discusses several productions from last year's festival program (competition and additional shows) in the context of social crisis and the aesthetics of the grotesque in drama and theatre. One outstanding example is the winner of the Borštnikovo Grand Prix, Crazy Locomotive directed by Jernej Lorenci, while other shows exhibited performance aesthetics as a strong tradition in Slovenian theatre (Oliver Frljić, Dragan Živadinov, Irena Tomažin).